Assessment of anti-inflammatory drugs in the rat using subcutaneous implants of polyurethane foam impregnated with dead tubercle bacilli. Issue 4 (August 1975) - Clarke, A K; Vernon-Roberts, B; Currey, H L
Abstract : The fluid and cellular phases of inflammatory resonse have been measured using a technique employing subcutaneous implantation of polyurethane foam cubes impregnated with heat-killed Mycobacterium tuberculosis. Phenylbutazone, azathioprine, aspirin, cyclophosphamide, and prednisolone suppressed fluid response, whereas sodium aurothiomalate, hydroxychloroquine, and D-penicillamine had no effect. All the drugs used suppressed the infiltration of inflammatory cells into the cubes.